A Benzenediamine Analog FC-99 Drives M2 Macrophage Polarization and Alleviates Lipopolysaccharide- (LPS-) Induced Liver Injury. (31st July 2019) - Gong, Wei; Zhu, Haiyan; Lu, Li; Hou, Yayi; Dou, Huan
Abstract : Macrophages have variable functional phenotypes, high diversity, and plasticity and are involved in the pathogenesis of sepsis-induced liver injury. Alteration of macrophage polarization through activated (M1) macrophage to alternatively activated (M2) macrophage has emerged as a potential therapeutic strategy. This study was designed to explore the effect of a benzenediamine analog FC-99 on macrophage polarization in vitro and lipopolysaccharide- (LPS-) induced liver injury followed by the underlying mechanisms. For in vitro experiments, FC-99 inhibited M1-related macrophage factors and promoted M2-related markers induced by IL-4 in the mouse macrophage cell line RAW264.7. Moreover, FC-99-induced macrophages polarized to M2 phenotype which could be repressed by a PPAR- γ inhibitor but not STAT6 siRNA knockdown, indicating FC-99-induced M2 macrophage polarization through PPAR- γ rather than STAT6 signal. In LPS-induced septic mice, FC-99 pretreated mice displayed lower expression of M1 markers together with the increased M2 marker CD206 and improvement of liver injury. These findings illustrated that FC-99 could promote M2 macrophage polarization via PPAR- γ signaling and seemed to be a potential therapeutic candidate for inflammatory liver injury.